Capsaicin and its Human Therapeutic Development - Mozsik, Gyula (IntechOpen, 2018)
The enormous field of this topic is clearly shown by the following facts: during the last ten years (2007-2016) around 500 papers/ year and 523 review articles are listed in the PubMed database on capsaicin, and over 200/year are under keywords of "capsaicin human". Recently, two major studies on the mortality of consumers of spicy food containing capsaicin and nonconsumers (over 350000 men and women aged 30-79 with heart disease, cancer, and stroke at baseline over 3.5 million person-years, 2004-2013) showed that the relative risk in total mortality was reduced by 14% in 10 diverse geographic areas of China (2015). Similarly, in the USA, (16,179 participants during over 2,70,000 person/year with the median of 18.9 years) the total mortality was reduced by 13% in populations consuming hot chili (2017). Recently, the book series "Progress in Drug Research" the 68th volume dealt for the first time on "Capsaicin as a Therapeutic Molecule" (Springer, Basel, 2014). Five excellent chapters are found in this book dealing with procedures of capsaicin from capsicum plants, emerging technologies to improve capsaicin delivery, capsaicinoid diversity and its human food preference, capsaicin and lipid metabolism, and predictors in treatment response to capsaicin. The results of these observations clearly indicate that the capsaicin research has changed direction to include human medical treatment with capsaicin. The book gathers knowledge from experts in basic and clinical sciences, pharmacologists, in the nutrition and food industry, in the drug industry, technologists, plant cultivators, as well as experts across a wide scale of medical branches.